Drawing on Space : Silke Schatz Nasreen Mohamedi Julie Mehretu Oliver Zwink Paul Noble Katja Davar Bjarni Thorarinsson Russell Crotty Takehito Koganezawa Graham Gussin Max Neuhaus Alan Johnston Tomoko Takahashi. - Doyle, Mary; Macfarlane, Kate; Stout, Katharine; Watson, Grant; The Drawing Room, London (London : The Drawing Room, 2002)
Schatz, Silke ; Mohamedi, Nasreen ; Mehretu, Julie ; Zwink, Oliver ; Noble, Paul ; Davar, Katja ; Thorarinsson, Bjarni ; Crotty, Russell ; Koganezawa, Takehito ; Gussin, Graham et al.
Drawing on Space, The Drawing Room, London, 19 June - 27 July 2002
kunstcatalogus